On understanding of proof in English and American law - O. V. Tiaglo (Bulletin of Kharkiv National University of Internal Affairs)
This research paper is devoted to explication of understanding of proof in English and American law by means of study of its evolution and current condition. To get this aim the comparative analysis of few similar fragments from the Black’s law dictionary is completed.